2004
DOI: 10.1038/sj.ejhg.5201292
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between obesity-susceptibility loci in chromosome regions 2p25-p24 and 13q13-q21

Abstract: One of the chief complexities of genetic influences on human obesity appears to be gene-gene interactions. Here, we employed model-free approaches to look for gene-gene interaction effects in human obesity using genome scan data from 260 European American families. We found consistent evidence for statistical interaction between 2p25-p24 (18 -38 cM) and 13q13-q21 (26-47 cM). For discrete traits, the positive correlations were significant at Po0.0001 (Pr0.0023 after correction for multiple tests) in both IBD-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…9,12,14,[30][31][32][33][34] In this regard, the current study showed that LPL Ser447Stop polymorphism, despite its functional role in promoting increases in LPL and the attendant lipid storage in adipocyte, 17,35 beneficially modified the association between obesity and the ADRB1 Arg389Gly polymorphism, particularly in white subjects. In the total sample, interactions between the two polymorphisms were significant in adulthood and for the longitudinal change.…”
Section: Discussionmentioning
confidence: 61%
“…9,12,14,[30][31][32][33][34] In this regard, the current study showed that LPL Ser447Stop polymorphism, despite its functional role in promoting increases in LPL and the attendant lipid storage in adipocyte, 17,35 beneficially modified the association between obesity and the ADRB1 Arg389Gly polymorphism, particularly in white subjects. In the total sample, interactions between the two polymorphisms were significant in adulthood and for the longitudinal change.…”
Section: Discussionmentioning
confidence: 61%
“…36 Dichotomous BMI (430) mapped to the nearby region with LODs 42. [37][38][39] Promising linkage was detected for metabolic syndrome phenotypes on 1p34.1 and suggestive linkage was found on 9q21.1 in blacks. 40 Chromosome 18 D18S59 D18S63 D18S452 D18S464 D18S53 D18S478 D18S1102 D18S474 D18S64 D18S68 D18S61 D18S1161 D9S288 D9S286 D9S285 D9S157 D9S171 D9S161 D9S1817 D9S273 D9S175 D9S167 D9S283 D9S287 D9S1690 D9S1677 D9S1776 D9S1682 D9S290 D9S164 The Viva La Familia Study G Cai et al candidate gene on chromosome 9 is fructose-1,6-bisphosphatase 2 (FBP2) which is involved in glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between different genetic 415 factors may also be important. If so, this causes some fundamental problems for geneticists (see Section 6.1).…”
Section: Genewatch Uk January 2006mentioning
confidence: 99%